1993
DOI: 10.1159/000175867
|View full text |Cite
|
Sign up to set email alerts
|

Does the Predictive Value of Baseline Coronary Risk Factors Change over a 30-Year Follow-Up?

Abstract: The association of baseline serum total cholesterol, systolic blood pressure, smoking and body mass index with coronary heart disease (CHD) mortality was analyzed among 1,619 men aged 40-59 at baseline. Analyses were made separately for the first, second and third decade of follow-up. Serum cholesterol and smoking more than 9 cigarettes daily were strong predictors of risk of CHD death (n = 450) occurring early and late during the 30-year follow-up. After 20 years of follow-up, systolic blood pressure was no l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
39
2

Year Published

1994
1994
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(49 citation statements)
references
References 10 publications
(22 reference statements)
8
39
2
Order By: Relevance
“…On the other hand, it has been shown that in the Finnish cohorts the lighter smokers in 1959 quit smoking during follow-up more often than heavier smokers. 34 It is unclear to what extent this phenomenon played a role in the time period we studied and in the other cohorts included. However, we did check whether light smokers consumed more fruits and vegetables at baseline because this may have led to bias.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…On the other hand, it has been shown that in the Finnish cohorts the lighter smokers in 1959 quit smoking during follow-up more often than heavier smokers. 34 It is unclear to what extent this phenomenon played a role in the time period we studied and in the other cohorts included. However, we did check whether light smokers consumed more fruits and vegetables at baseline because this may have led to bias.…”
Section: Discussionmentioning
confidence: 98%
“…It is questionable how predictive a single measurement is. We know that during follow-up, changes in both diet and smoking habits occurred (for Finland, see Pekkanen et al 34 ). Fruit and vegetable consumption increased in all 3 countries, mostly in Italy.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, if future risk profiles are related to the association between obesity and mortality, adjustment for any of these during follow-up would bias assessment of the true mortality risk associated with obesity. A high degree of correlation of BMI measured throughout adult life (30) and the uncertain long-term effects of weight loss interventions (2) support the rationale for identifying BMI in adulthood as a target for prevention. Our study confirms that the relative risk for death associated with increased BMI in adulthood remains relatively constant throughout life (12,31).…”
Section: Discussionmentioning
confidence: 99%
“…13 There are no previous reports from prospective studies on the association of risk factors assessed in middle age and later in life with the occurrence of carotid atherosclerosis in old age.…”
Section: -10mentioning
confidence: 99%